Deep economic integration and state capacity: A mechanism for avoiding the middle-income trap? - László Bruszt; Nauro F. Campos (Asian Development Bank (ADB), 2018)
Exiting the middle-income trap entails costly improvements in state capacity. That deep economic integration induces powerful actors to support increasing state capacities remain underresearched. Here we ask: Under what conditions can deep economic integration yield increases in state capacity? We measure institutional change in 17 European former communist countries exposed to similar challenges of deep integration (European Union membership candidates), and find large variation in the evolution of their state capacities. To understand this variation, we put forward a conceptual framework and supporting hypotheses. From testing these, we empirically identify key relationships and specific reform implementation sequences. Our main result is the centrality of an intricate relationship between bureaucratic independence and judiciary capacity as a main driver of institutional change. Change in these two institutional fields, we find, is a precondition for increasing internal and external competition, which are key factors for successfully escaping the middle-income trap.
Keywords: D85; H41; O17; O18; 330; institutions; middle-income trap; state capacity